Cosolvent and Crowding Effects on the Temperature‐ and Pressure‐Dependent Dissociation Process of the α/β‐Tubulin Heterodimer. Issue 9 (18th April 2019) - Schummel, Paul Hendrik; Anders, Christian; Jaworek, Michel W.; Winter, Roland
Abstract: The front cover artwork illustrates that by adjusting the level of natural cosolutes like TMAO, the deteriorating effect of deep‐sea hydrostatic pressures on tubulin association can be suppressed. Read the full text of the Article at10.1002/cphc.201900115 . Abstract : "We explore the effects of different types of cosolvents, such as trimethylamine‐ N ‐oxide (TMAO), sucrose and urea, and crowding agents to mimic cell‐like conditions, on the temperature and pressure stability of the building block of microtubules…" This and more about the story behind the front cover can be found in the Article at10.1002/cphc.201900115 .